Angiotensin II Type I Receptor Blockade Is Associated with Decreased Cutaneous Scar Formation in a Rat Model. Issue 5 (November 2019) - Murphy, Amanda; LeVatte, Terry; Boudreau, Colton; Midgen, Craig; Gratzer, Paul; Marshall, Jean; Bezuhly, Michael
Abstract : Background: Angiotensin II engagement of angiotensin II type 1 receptor (AT1R) is implicated in fibrogenesis, with AT1R blockers used clinically to attenuate cardiac and renal fibrosis. The authors tested the hypothesis that the AT1R blocker losartan could reduce postsurgical cutaneous scarring in rats. Methods: Human dermal fibroblasts were treated with losartan and assessed for viability, contractile activity, migration, and profibrotic gene transcription by means of calcein, collagen gel, scratch, and quantitative reverse transcriptase polymerase chain reaction assays, respectively. Monocyte migration and adhesion to losartan-treated and control fibroblasts were examined. Losartan effects in vivo were assessed using a mechanical distraction hypertrophic scar model. Three days after incisions were made and closed on their backs, rats were assigned randomly to receive drinking water with or without losartan (1 mg/kg per day; n = 6 per group). Distraction devices were applied and activated up to day 14. On day 28, scars underwent cross-sectional area and elevation index analyses, and α-SMA + (alpha-smooth muscle actin) and CD68 + (monocyte/macrophage marker) immunostaining. Results: Losartan-treated human dermal fibroblasts displayed decreased contractile activity, migration, and gene expression of transforming growth factor-β1, collagen I, and monocyte chemoattractant protein-1 relative to controls ( p < 0.05). Monocyte migration and adhesion to losartan-treated fibroblasts were reduced ( p < 0.01). Compared to controls, scars from losartan-treated rats demonstrated decreased cross-sectional area (19.4 ± 3.1 mm 2 versus 45.0 ± 5.2 mm 2 ; p = 0.002), elevation index (1.5 ± 0.1 versus 2.6 ± 0.3; p = 0.003), and α-SMA + and CD68 + immunostaining ( p < 0.001). Conclusions: Losartan decreases myofibroblast activity and reduces monocyte trafficking to cutaneous scar. These findings support losartan as a potential novel therapy for the prevention of hypertrophic scars. Abstract : Supplemental Digital Content is available in the text.